Analisis Rasio Profitabilitas Dan Rasio Aktivitas Sebagai Dasar Penilaian Kinerja Keuangan PT. Sepatu Bata Tbk - Indah Ivanka; Muhammad Yafiz; Arnida Wahyuni Lubis (Pusat Riset dan Inovasi Nasional, 2024)
PT Shoes Bata Tbk is a company engaged in the manufacture of leather shoes, canvas shoes, casual and sports shoes, injection/slop sandals and industrial footwear safety mats. Financial performance is a description of the financial condition of a company which is analyzed using financial analysis tools, usually the measure used is the ratio. Research conducted by the author to analyze the financial performance of PT Shoes Bata Tbk based on profitability ratios and activity ratios. The profitability ratio can be measured by Gross Profit Margin, Net Profit Margin, and Return on Investment. Where Gross Profit Margin and Net Profit Margin are ratios that measure the company's ability to earn profits on sales, Return on Investment is a ratio that measures the company's ability to use all assets owned to generate profits after tax. The activity ratio can be measured by Receivable Turnover, which is a ratio that measures the company's ability to quickly manage the level of accounts receivable turnover. Inventory Turnover is a ratio that shows how quickly inventory turns over in sales activities. And Total Asset Turnover is a ratio that measures a company's ability to create sales using all the assets it owns. The aim of this research is to find out and analyze the financial performance of PT SEPATU BATA Tbk during 2016-2021 based on the two ratios. This research uses a descriptive qualitative approach method. The data source used is secondary data in the form of profit/loss financial report data and balance sheet reports. The results of this research indicate that the financial performance of PT Shoes Bata Tbk for the 2016-2021 period based on GPM is considered very good because the company was able to reduce the cost of goods sold, resulting in high sales and high gross profit. NPM is considered not good because the net profit generated is less with quite high sales. ROI is considered very poor because the high total assets are not commensurate with the net profit generated. RT is considered very good because it increases every year. IT is considered very poor due to the decrease in cost of goods sold and increase in average inventory each year. TAT is considered quite good because the company is able to manage its assets well. Financial performance as measured by the profitability ratio and activity ratio can be said to be less efficient, because the components of the profitability ratio and activity ratio are still low and do not reach good company standards.